Range of therapeutic metformin concentrations in clinical blood samples and comparison to a forensic case with death due to lactic acidosis. (May 2018) - Hess, C.; Unger, M.; Madea, B.; Stratmann, B.; Tschoepe, D.
Highlights: Metformin serum concentrations in 95 diabetics on chronic use. No correlation between plasma concentration and glomerular filtration rate. A post mortem case with death due to lactic acidosis is described. Abstract: Due to a lack of reference values for blood concentration of metformin in the literature, the forensic evaluation of metformin findings in blood samples is difficult. Interpretations with regard to the assessment of blood concentrations as well as an estimation of the ingested metformin amounts are often vague. Furthermore, post mortem evaluation of death due to lactic acidosis because of metformin is difficult since renal performance or lactate concentrations can not always reliably be determined after death. To describe a concentration range in clinical samples after chronic use of metformin, metformin serum concentrations were determined in serum samples of 95 diabetic patients receiving daily doses of 500 mg–3000 mg of metformin. The analyses of metformin was carried out using a validated high performance liquid chromatograph coupled to triple quadrupole mass spectrometry (LC–QQQ-MS). On average, metformin concentrations were 1846 ng/mL (<LoQ—5560 ng/mL) and independent of the prescribed daily dose. There was no correlation between plasma concentration and glomerular filtration rate except for the 1700 mg daily dose collective (R 2  = 0.707). Results of the herein presented study are useful for the interpretation of analytical metformin findings in forensic toxicology. The utility of the described concentration range is demonstrated by discussing a death case involving a fatal lactate acidosis after metformin intake and renal failure. Usefulness of the parameters metformin blood concentration, lactate concentration and glomerular filtration rate in post mortem cases of lactic acidosis due to metformin intoxication are discussed.